Financial Ratios Impact: Bond Ratings in Indonesian Stock Exchange Manufacturing Companies: Pengaruh Rasio Keuangan terhadap Peringkat Obligasi: Studi pada Perusahaan Manufaktur di Bursa Efek Indonesia. - Lailatul Mas’adah; Wiwit Hariyanto (Universitas Muhammadiyah Sidoarjo, 2024)
This study aimed to investigate the impact of Retained Earning, Growth of Company, and Interest Coverage Ratio on bond ratings of manufacturing companies listed in the Indonesian Stock Exchange. The study used a quantitative approach with a sample of 104 bonds issued by seven companies that were rated by PEFINDO from 2014 to 2017. The data were analyzed using logistic regression analysis and processed using SPSS 18. The results showed that Retained Earning, Growth of Company, and Interest Coverage Ratio had a significant simultaneous effect on bond ratings. However, Retained Earning and Interest Coverage Ratio had a partial effect on bond ratings, while Growth of Company had no effect. This study implies that investors and bond issuers should pay attention to these financial ratios to make informed investment decisions.Highlights : Financial ratios are essential tools for evaluating the health and performance of manufacturing companies. Bond ratings are influenced by financial ratios such as Retained Earning, Growth of Company, and Interest Coverage Ratio. Logistic regression analysis can be used to determine the simultaneous and partial effects of financial ratios on bond ratings, providing valuable information for investors making informed investment decisions. Keywords: financial ratios, bond ratings, manufacturing companies, investment decisions, logistic regression analysis.